NILAI-NILAI PENDIDIKAN ISLAMÂ DALAM TRADISI MALAM JUM`AT LEGI di SUWAYUWO SUKOREJO PASURUAN - Wiwin Fachrudin Yusuf (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Indonesia is a country which is rich in traditions, such as the Friday night legi tradition. The Friday night legi tradition is a tradition that is preserved by the community, especially in the Javanese community in Pasuruan Regency, Sukorejo District and especially in Suwayuwo Village. The values of Islamic education are a clear conception, to be expressed and implied from a certain person or group of what is desired which i nfluences the choice and purpose of action. Friday night Legi is Legi market day which is believed by people to come to the mosque to carry out gathering and prayer with the aim of worshiping Allah SWT. Where this Friday night leg is called the night on Fr iday which some people might consider a very special night compared to other Fridays. The formulation of the problem in this study is the values of Islamic education in the Friday night Legi tradition in Suwayuwo Sukorejo Pasuruan, and the public's view of the Friday night tradition of Legi in Suwayuwo Sukorejo Pasuruan. This study uses a qualitative approach with a descriptive type. There are two data in this study covering primary data, and secondary data. The data were collected using in - depth intervie ws, participant observation, and documentation studies. Triangulation is a data analysis technique used in this study. Meanwhile, checking the validity of the data findings is carried out by means of persistence/consistency in observation. The results of t his study indicate that: (1) the values of Islamic education in the Friday night Legi tradition in the village of Suwayuwo, namely the value of monotheism, and society (2) the community's view of the Friday night tradition of Legi that the community is v ery enthusiastic, and they think that the night on Friday is very special compared to other Friday nights.